The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1071/sb15038
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of the green ash eucalypts (Myrtaceae): a tale of reticulate evolution and misidentification

Abstract: Abstract. Eucalyptus is a genus that occurs in a range of habitats in Australia, Papua New Guinea, Timor, Sulawesi and the Philippines, with several species being used as sources of timber and fibre. However, despite its ecological and commercial significance, understanding its evolutionary history remains a challenge. The focus of the present study is the green ashes (subgenus Eucalyptus section Eucalyptus). Although previous studies, based primarily on morphology, suggest that the green ashes form a monophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 76 publications
4
23
0
Order By: Relevance
“…The phylogeny of the green ashes was previously estimated using the DArT microarray method (Rutherford et al 2016). It was found that while some of the lineage relationships were consistent with previous taxonomic classifications primarily based on morphology, other relationships were not.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The phylogeny of the green ashes was previously estimated using the DArT microarray method (Rutherford et al 2016). It was found that while some of the lineage relationships were consistent with previous taxonomic classifications primarily based on morphology, other relationships were not.…”
Section: Introductionmentioning
confidence: 56%
“…The advent of next-generation sequencing (NGS) and associated technologies has enabled a much higher genomic resolution for the study of speciation mechanisms compared with traditional molecular methods (Keller et al 2013). One technique that is increasingly being used in Eucalyptus is Diversity Arrays Technology sequencing (DArT, e.g., Steane et al 2011;Rutherford et al 2016). DArT is based on genome complexity reduction using restriction enzymes, followed by hybridisation to microarrays to simultaneously assay thousands of markers across the genome (Jaccoud et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Much more data than the four loci used here will be necessary to achieve higher resolution of the eucalypt relationships. Previous eucalypt studies using a greater proportion of the 55 nuclear or plastid genome than in the present study have still led to non-monophyly of lower-level groups (Nevill et al 2014;Rutherford et al 2015;Jones et al 2016). It may be possible to resolve relationships in cases of incomplete lineage sorting using a coalescent approach, which is being improved in programs such as STAR BEAST (ver.…”
Section: Resolution Of Lower-level Classificationmentioning
confidence: 82%
“…Further, the hybridising ability of what are considered to be more distantly related groups, as also illustrated by Schuster et al (2018), means that a resolved bifurcated tree might not be appropriate, and that nodes closer to the tips of the phylogeny might be better represented as evolutionary networks (e.g. appendix 4 of Rutherford et al 2015).…”
Section: Resolution Of Lower-level Classificationmentioning
confidence: 99%
“…et al 2006Parra-O. et al , 2009, microsatellites Ochieng et al 2007b), AFLPs (McKinnon et al 2008), and Diversity Array Technology (DArT) markers Woodhams et al 2013;Hudson et al 2015;Rutherford et al 2015).…”
Section: Morphological and Molecular Phylogeniesmentioning
confidence: 99%